RESILIENCE CONVEYED THE READINESS FOR ENHANCING SELF-HEALTH MANAGEMENT OF ACUTE ISCHEMIC STROKE PATIENTS IN THE ERA OF THE COVID-19 PANDEMIC:A CASE STUDY - Suwaryanti Suwaryanti; Fitria Handayani; Nur Setiawati Dewi (P3M Universitas 'Aisyiyah Surakarta, 2023)
Introduction: The COVID-19 pandemic is a disease globally that affects acute ischemic stroke patient ability to survive from adversity. Self-management is needed to determine the readiness of patients with ischemic stroke acute to recover from physical weakness during the pandemic COVID-19. Objective: To describe the case of resilience in conveying the readiness for enhancing of self-health management patient ischemic stroke acute during the pandemic COVID-19. Clinical observation: An evaluation was about readiness to accept health management during the pandemic COVID-19 in patients with stroke ischemic acute. The important things to readiness of health management: self-acceptance, family support, and self-exercise at home. Interventions: Focused on health education to do self-exercise during the pandemic COVID-19 to recover them due to limb weakness. Conclusion: Outcome criteria showed that there was increasing in exercise to reduce the risk factor, implementation of a self-care program, and life activity more effectively to fulfill health goal increase.